Compact Two-Section Half-Wave Balun Based on Planar Artificial Transmission Lines - Changjun Liu; Zhenyu Yin; Yilan Yang; Wen Huang (International Journal of Antennas and Propagation)
Artificial transmission lines are realized by a series of meandered-line inductors, parallel-plate capacitors, and interdigital capacitors, which belong to metamaterial transmission lines. An ameliorated artificial transmission line is proposed to realize a low characteristic impedance transmission line. A two-section half-wave balun at 900 MHz is designed, fabricated, and measured in this paper. The compact balun is based on conventional and ameliorated planar artificial transmission lines instead of microstrip transmission lines. The main advantage of the proposed balun is its size reduction, which occupies only about 10% of a conventional one. Measured results match well with theory and simulation. The balun features excellent amplitude and phase balance in microwave power combining and a reasonable bandwidth of the return loss as well.